PERUBAHAN BEBERAPA SIFAT KIMIA TANAH PESISIR DAN PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) YANG DIBERI PUPUK KANDANG AYAM - SAFITRI, ASRIANI; GINTING, SAHTA; ANAS, ARSY AYSYAH (Jurnal Agroteknos, 2022)
This study aimed to determine the changes in some chemical properties of coastal soil and the growth of pakcoy (Brassica rapa L.) given chicken manure and to obtain a treatment that changed the chemical properties of coastal soil and the growth of pakcoy (Brassica rapa L.) was more good. This study used a randomized block design (RBD) consisting of 4 treatments, namely A0 (without chicken manure), A1 (100 g chicken manure polybag-1), A2 (200 g chicken manure polybag-1), and A3 (300 g chicken manure polybag-1). Soil analysis was carried out at the Nanotechnology Laboratory, Halu Oleo University. This study showed that chicken manure increased the nutrient content of total N-, P-available, C-organic, and pH in coastal soil, with a dose of organic fertilizer that gave the best effect, namely 100 g polybag-1.